Czy smutny i ckliwy potrafi się cieszyć? Rzecz o Grzegorzu z Nazjanzu - Zagórski, Dariusz (Vox Patrum, 2012)
This article is aimed as an objective description of the character of Gregory of Nazianzus, written in the light of the realities of life and spiritual experience, which may revise the existing opinions about the Author, relating to his personality, attitude and choices, as they are often one-sided, unjust and wrongful. This study presents Gregory as pastor concerned for the Church who grieves for its internal tearing as well as for „his colleagues in episcopacy” self-interest. It treats about personal aspects of his life often marked by suffering and difficult experience. In this context, the article also points to the source of joy and optimism of life, which is support for the needy and those who lost the meaning of life.